2016
DOI: 10.1021/acs.iecr.6b03230
|View full text |Cite
|
Sign up to set email alerts
|

Radium-226 Removal from Simulated Produced Water Using Natural Zeolite and Ion-Exchange Resin

Abstract: Large volumes of produced water with high dissolved solids content are generated by the oil and gas industry. The presence of naturally occurring radioactive materials (NORM), such as radium, in this flowback water adds to the costs associated with its handling, treatment, and disposal. In this research, clinoptilolite was tested for radium removal and its performance has been compared to that of an ion-exchange resin. Natural zeolite showed excellent stability in high chloride environments; its capacity and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Brandt et al showed that radium uptake by dissolution–recrystallization of barite can be higher than the values observed in this study but this process is extremely slow, and it can take up to 1 year to achieve equilibrium. Hence, it is reasonable to disregard dissolution–recrystallization as a possible mechanism for radium uptake in this study that was conducted over a period of 24 h. The concentration of surface sites is a possible reason for the higher Ra-226 uptake by celestite than barite , since BET analysis showed that the specific surface area of celestite (i.e., 0.58 m 2 /g) is significantly higher than that of barite (i.e., 0.17 m 2 /g). The higher measured surface area of celestite can be explained by the tendency of barite particles to agglomerate (Figure S2d in Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Brandt et al showed that radium uptake by dissolution–recrystallization of barite can be higher than the values observed in this study but this process is extremely slow, and it can take up to 1 year to achieve equilibrium. Hence, it is reasonable to disregard dissolution–recrystallization as a possible mechanism for radium uptake in this study that was conducted over a period of 24 h. The concentration of surface sites is a possible reason for the higher Ra-226 uptake by celestite than barite , since BET analysis showed that the specific surface area of celestite (i.e., 0.58 m 2 /g) is significantly higher than that of barite (i.e., 0.17 m 2 /g). The higher measured surface area of celestite can be explained by the tendency of barite particles to agglomerate (Figure S2d in Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Greatest reductions in total radium concentrations from hydrant to tap were observed when water softening or reverse osmosis was used for treatment relative to cases with no treatment. Water softening, particularly with zeolite-based (Clinoptilolite) systems, was shown by Fan et al (2016) to be effective at removal of Ra over other alkali-earth cations. Zeolitic systems are more selective over ion exchanges resins, with Ba identified as the major competitor for absorption sites.…”
Section: Winter 2020-2021 Private Well Studymentioning
confidence: 99%
“…Within strong acid cation exchangers, such as sulfonic acid resins, the affinity for the alkali earth cations is Ba 2+ > Sr 2+ > Mg 2+ > Ca 2+ (Hubicki & Kołody nska, 2012). For these resins, binding increases with higher charge (Ca 2+ > Na + ) and increasing atomic number for cations of the same charge (Fan et al, 2016). Weak acid cation resins utilize carboxylate ligands where the affinity trend is reversed from the strong acid resins; smaller alkali earth cations (e.g., Mg 2+ and Ca 2+ ) would be removed preferentially over the larger ones, such as Ba 2+ or Ra 2+ (Sorg et al, 1980).…”
Section: Winter 2020-2021 Private Well Studymentioning
confidence: 99%
“…As another example, the interaction of the salt in the shale water with the surrounding rocks can mobilize radionuclides (Rich and Crosby, 2013). This results in a high concentration of radium-226 in some PW (Fisher, 1998;Osborn et al, 2011;Fan et al, 2016). Although water treatment approaches could reduce radioactive contamination by more than 90% (Rich and Crosby, 2013;Brown, 2014), chronic exposure to the remaining radium-226 contamination in drinking water can pose serious health risks such as cancer, anemia, and dental fractures (Rich and Crosby, 2013;Warner et al, 2013;Brown, 2014).…”
Section: Introductionmentioning
confidence: 99%